Padrões de distribuição da vegetação florestal na Serra do Caverá - sudoeste do Rio Grande do Sul/Brasil - Guadagnin, Paula Mirela Almeida (2019)
Although it is favored by the current climatic conditions, the forest vegetation is not predominant in the landscape, in the South-Rio-Grandense territory, as is the country. Nevertheless, in some places forest formations develop successfully as in the Serra do Caverá region in the southwest of Rio Grande do Sul. The objective of this work is to understand how the distribution of forest vegetation occurs and what factors contribute to its establishment in Serra do Caverá, proposing possible patterns for the advance of the forest vegetation in the region. The mapping of the forest vegetation and the relief of the study area, from its forms, elements and components of the slopes, were performed using an MDE generated from the SRTM data and worked on the ArcGIS 10.3 GIS, from which the correlations, as well as fieldwork for data collection and verification. It was also used the calculation of the frequency ratio, statistical method used to demonstrate the correlation of the forest vegetation with the attributes analyzed. The results showed that the distribution and establishment of forest vegetation in the Serra do Caverá and surrounding areas is due to some attributes of the relief, such as flat forms, valleys, flat, moat where riparian forests occur and from where the vegetation advances to the associations of hills and so - called morrotes of Serra do Caverá, through the bases of slopes, excavated elements and slopes with profile of concave curvature and plane of convergent curvature. Thus, it is possible to infer that the forest vegetation in the study area presents patterns in its advance over the predominantly rural areas that occurs, mainly, from the riparian forests, where besides the water availability, the forest vegetation finds edaphic conditions favorable to its establishment, and extends from the riparian forests to the slope bases, from where it advances to the upper portions of the steeper slopes, through the concave slopes, excavated reliefs and rocky contacts, especially when there is possibility of water in the slopes.